Indun Analizing Skills Terhadap Pemecahan Masalah Siswa Materi Alat Ukur Jangka Sorong Kelas X Konsentrasi Keahlian TKR SMKN 1 Bendo Magetan - Mahmudah, Indun (LP. Ma'arif Janggan Magetan, 2024)
This research is a descriptive study that aims to determine the description of the Analyzing Skills Ability, towards the ability to solve problems in the subject of Natural Sciences, material on Vernier Caliper Measuring Instruments for class X, concentration of expertise TKR SMKN 1 Bendo Magetan and specifically to find out the description of the steps to solve Physics problems of students. The sample in this study was 30 students. The research instrument used was a test of the ability to solve Natural Sciences problems that have been validated for use. The results of the descriptive analysis show that the level of ability to solve Natural Sciences problems through Analyzing Skills has a positive and significant influence on Students' Understanding of Vernier Caliper Measuring Instruments in the Subject of Natural Sciences, Concentration of Expertise TKR at SMKN 1 Bendo Magetan. Analyzing skills simultaneously have a contribution of only 0.0352% towards Students' Understanding of Vernier Caliper Measuring Instruments in the Subject of Concentration of Expertise TKR at SMKN 1 Bendo Magetan, in general students are able to complete 3 indicators of solving problems, namely the ability to understand problems, the ability to describe problems, and the ability to design solutions to problems. While for other indicators, students have not been able to complete them well.